Dowcip językowy w felietonistyce (na przykładzie felietonów Marcina Prokopa) = A linguistic joke in the newspapers` columns (on the example of Marcin Prokop) - Nawlicka, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article focuses on the stylistic devices used in a linguistic joke in Marcin Prokop`s feuilletons in order to present what a linguistic joke is in the newspapers` columns. The definitions of the feuilleton itself and individual stylistic devices as well as the profile of a columnist journalist, based on the example of Marcin Prokop, were also presented. The stylistic devices were grouped into the functions assigned to them in the linguistic joke.
Keywords: felieton; dowcip językowy; środki stylistyczne; metafora; anegdota; porównania; intertekstualność; kolokwializm; column; linguistic joke; stylistic devices; metaphor; anecdotes; comparisons; intertextuality; colloquialism